FITOREMEDIASI LOGAM BERAT KADMIUM (CD) DALAM TANAH DENGAN MENGGUNAKAN BAYAM DURI (AMARANTHUS SPINOSUS L) - Mohamad, Erni (Sainstek, 2011)
Cadmium waste is the result of industrial processes that are carcinogen material. The target organs of Cd toxicity is the kidney and liver. Cadmium waste treatment can be done by adsorption method using a plant thorn spinach (Amaranthus spinosus L). This herb has been used as an adsorbent because it contains proteins that have the amine group (-NH2), carboxyl group (-COOH), also sulfidril group (-SH). Besides, in plant tissue have a cell wall composed of cellulose, lignin-containing hydroxyl group (-OH). Polar clusters are able to bind heavy metals. The purpose of this study was to determine the ability of absorption of spinach plants with thorns as phytoremediation of metal cadmium (Cd) in tissues of roots, stems and leaves. The study was conducted with various concentration (25, 50) ppm Cd without EDTA and (25, 50) ppm Cd with EDTA. The concentration of cadmium adsorbed by plant tissue was analyzed using atomic absorption spectrophotometry (AAS) at wavelength 228.8 nm. The data were then analyzed RAL. The order of adsorption ability of the highest plant tissue concentrations of spinach with thorns on the leaves of 25 ppm Cd (7.659)> stem (6.419)> root (5.585) and at a concentration of 50 ppm Cd is the leaves (5.589)> root (5.228)> stem (4.320). At the highest concentration variation of Cd (II) adsorbed to 25, 50 ppm without EDTA and EDTA on each network is at 25 ppm of leaves (7.659